Policy Analysis of Institutional Capacity Building at the Department of Women's Empowerment and Child Protection in Bintan Regency - Defitriyani, Defitriyani (Journal Governance Society, 2024)
This study aims to analyze the institutional capacity-building policy at the Department of Women’s Empowerment, Child Protection, Population Control, and Family Planning (DP3KB) in Bintan Regency. The background of this research is the importance of institutional capacity building as an effort to strengthen public services and meet community needs in the fields of women’s empowerment and child protection. The research method used is qualitative descriptive with a case study approach. Data collection was conducted through interviews, observations, and document analysis, which were then analyzed using pattern matching techniques and explanation development based on Grindle's capacity development theory. The results of the study indicate that DP3KB faces challenges such as limited human resources, inadequate budget allocation, and suboptimal organizational structures. Nevertheless, efforts to strengthen institutional capacity include staff training, strengthening internal mechanisms, and synergy with other institutions. In conclusion, institutional capacity-building policies encompassing dimensions of human resource development, organizational strengthening, and comprehensive institutional reform are required to improve the effectiveness of DP3KB services in Bintan Regency. Additionally, periodic evaluations of implemented programs are essential to ensure the sustainability and positive impacts of these policies. Effective policy implementation through strategic planning, monitoring, and cross-sector collaboration is expected to realize the organization’s vision and mission in supporting fair and inclusive regional development.